2021
DOI: 10.3892/ijmm.2021.5041
|View full text |Cite|
|
Sign up to set email alerts
|

Knockdown of mesenchymal stem cell‑derived exosomal LOC100129516 suppresses the symptoms of atherosclerosis via upregulation of the PPARγ/LXRα/ABCA1 signaling pathway

Abstract: Mesenchymal stem cell (MSC) therapy has potential applications in treating atherosclerosis and coronary heart disease (CAD). Previous studies have demonstrated that MSCs are the most preferable sources of therapeutic exosomes, which carry long non-coding RNAs and participate in the progression of atherosclerosis. The results of our previous bioinformatics study demonstrated that the levels of LOC100129516 were significantly upregulated in peripheral blood mononuclear cells obtained from patients with CAD. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…The roles of ABCA1 and ABCG1, primary cholesterol efflux mediators, in limiting macrophage foam cell formation and atherogenesis have also been widely validated (Yvan‐Charvet et al, 2007). Previous studies showed that PPARγ/LXRα/ABCA1 axis mediates cholesterol efflux from macrophages and decreases foam cell formation (Jiang et al, 2017; Sun et al, 2021; Zheng et al, 2021). Chen et al demonstrated that Netrin‐1 inhibits ferroptosis by activating PPARγ/Nrf2/GPX4 signaling pathway in HT22 cells (Chen, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The roles of ABCA1 and ABCG1, primary cholesterol efflux mediators, in limiting macrophage foam cell formation and atherogenesis have also been widely validated (Yvan‐Charvet et al, 2007). Previous studies showed that PPARγ/LXRα/ABCA1 axis mediates cholesterol efflux from macrophages and decreases foam cell formation (Jiang et al, 2017; Sun et al, 2021; Zheng et al, 2021). Chen et al demonstrated that Netrin‐1 inhibits ferroptosis by activating PPARγ/Nrf2/GPX4 signaling pathway in HT22 cells (Chen, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the therapeutic research on cargo delivery strategies based on MSC-derived exosomes is becoming more and more extensive. The exogenous small interfering LOC100129516 was successfully delivered to THP-1 cells via MSC-derived exosomes, resulting in significantly lower levels of total cholesterol, free cholesterol, and cholesteryl ester in THP-1 macrophage-derived foam cells [98] . Finally, the progression of the disease was inhibited by modulating PPARγ/LXRα/ABCA1 signaling.…”
Section: Current Progress Of Exosome‐based Delivery Platform To Treat...mentioning
confidence: 99%
“…LncRNA LOC100129516 levels were found to be upregulated in macrophage-derived foam cells induced by oxidized low-density lipoproteins [ 74 ]. In an ApoE-/- atherosclerosis mouse model, exosomal delivery of small interfering RNA against LOC100129516 decreased total cholesterol and low-density lipoprotein levels through activation of the peroxisome proliferator-activated receptor γ (PPARγ)/liver X receptor α (LXRα)/phospholipid-transporting ATPase ABCA1 (ABCA1) signaling pathway, promoting cholesterol efflux and suppressing intracellular lipid accumulation [ 74 ].…”
Section: The Role Of Msc-derived Lncrnas In Cardiac Injury and Repairmentioning
confidence: 99%